A proposal for using contralateral teeth to provide well‐balanced experimental groups for endodontic studies. (16th October 2015) - Xu, J.; Shao, M. Y.; Pan, H. Y.; Lei, L.; Liu, T.; Cheng, L.; Hu, T.; Dummer, P. M. H.
Abstract: Aim: To develop a suitable protocol for screening extracted teeth so as to create anatomically well‐balanced experimental groups for endodontic studies. Methodology: Sixty pairs (120 teeth) of contralateral premolars (CLPs) were collected. The evaluation of samples for anatomical features was performed in the following ways. First, the 120 teeth were divided into right and left sides ( N  = 60, each side), and the teeth of each side were screened individually according to regular inclusion criteria (parameters included mature apical foramen, canal type, canal curvature and tooth length). The similarity of the specimens was then evaluated. The second screening process evaluated the 60 pairs of CLPs using the same criteria. Finally, CBCT was used to establish a strict screening protocol to create well‐balanced groups of CLPs. Results: In the first screening process, 80% (24/30) of the left and 61% (19/31) of the right side were selected out of teeth with mature foramina; but the included teeth had asymmetrical canal curvatures. In the second screening process, 28 pairs were selected after the exclusion of those with an immature foramen in one pair. Seventeen pairs in which the tooth length and canal curvature were symmetrical were selected from the 28 CLPs. In the third screening, only 21% (6/28) of CLPs passed the rigorous screening procedure and were identical for creating balanced experimental groups. Conclusions: Relatively, few pairs of contralateral teeth had anatomical symmetry. For endodontic studies, a strict and detailed scientific screening protocol is necessary to achieve well‐balanced experimental groups.